Development of Entrepreneurship Strategic Planning Model at Al-Fitrah Islamic Boarding School Surabaya - Saiful Irfan; Maria Veronika Roesminingsih; Mudjito Mudjito (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to describe 1) feasibility, 2) practicality, and 3) the effectiveness of the entrepreneurship strategic plan model at Al-Fitrah Islamic Boarding School Surabaya. The natural conditions in the three Islamic boarding schools provide educational services at low and affordable costs from the community. Contributions in addition to educational services, it is also necessary to consider contributions to economic activities in the Islamic boarding school. Method: This research is a development research with a Research and Development (R&D) approach. The subjects of research in developing entrepreneurial strategic planning models in Islamic boarding schools are Islamic boarding school caregivers, ustadz, and students of Al-Fitrah Islamic Boarding School Surabaya. Results: The development results in an entrepreneurship strategic plan book at the Al Fithrah Islamic Boarding School Surabaya, which has been used to reference business plans for business actors in the Al Fithrah Islamic Boarding School Surabaya. The effectiveness of using products in the form of entrepreneurship strategic plan books at the Al Fithrah Islamic Boarding School Surabaya can be seen from the results of each strategy map and business plan made during the entrepreneurship strategic plan preparation workshop. Novelty: The entrepreneurship strategic plan book provides an overview of strategic initiatives in response to the SWOT analysis that has been carried out. This strategic initiative provides the goals to be achieved and what strategies must be made to achieve these goals.